Fractal Robots: An Intelligent Futuristic Machine - Jha, Ketan (International Journal of Computer Sciences and Engineering, 2025)
Fractal Robots is a developing new administration that guarantees to alter each part of human innovation. This innovation has the potential to enter each field of human work like development, medication, research, and others. Fractal robots can empower structures to be worked inside a day, help perform touchy therapeutic operations and can aid research centre trials. Fractal Robots have worked in self-repair which implies they can proceed without human intercession. In this paper, I have shown a research article about an attractive technology called as fractal robot, this new technology has enough amazing features which can attracts many researchers and scientists for continuing their research work in this area.